Risk Factors for the Postoperative Recurrence of Instability After Arthroscopic Bankart Repair in Athletes. Issue 9 (5th September 2017) - Nakagawa, Shigeto; Mae, Tatsuo; Sato, Seira; Okimura, Shinichiro; Kuroda, Miki
Background: Several risk factors for the postoperative recurrence of instability after arthroscopic Bankart repair have been reported, but there have been few detailed investigations of the specific risk factors in relation to the type of sport. Purpose: This study investigated the postoperative recurrence of instability after arthroscopic Bankart repair without additional reinforcement procedures in competitive athletes, including athletes with a large glenoid defect. The purpose of this study was to investigate risk factors related to the postoperative recurrence of instability in athletes. Study Design: Case-control study; Level of evidence, 3. Methods: A total of 115 athletes (123 shoulders) were classified into 5 groups according to type of sport: rugby (41 shoulders), American football (32 shoulders), other collision sports (18 shoulders), contact sports (15 shoulders), and overhead sports (17 shoulders). First, the recurrence rate in each sporting category was investigated, with 113 shoulders followed up for a minimum of 2 years. Then, factors related to postoperative recurrence were investigated in relation to the type of sport. Results: Postoperative recurrence of instability was noted in 23 of 113 shoulders (20.4%). The recurrence rate was 33.3% in rugby, 17.2% in American football, 11.1% in other collision sports, 14.3% in contact sports, and 12.5% in overhead sports. The most frequent cause of recurrence was tackling, and recurrence occurred with tackling in 12 of 16 athletes playing rugby or American football. Reoperation was completed in 11 shoulders. By univariate analysis, significant risk factors for postoperative recurrence of instability included playing rugby, age between 10 and 19 years at surgery, preoperative glenoid defect, small bone fragment of bony Bankart lesion, and capsular tear. However, by multivariate analysis, the most significant factor was not the type of sport but younger age at operation and a preoperative glenoid defect with small or no bone fragment. Compared with the other sports, there was a significantly greater recurrence rate among rugby players without the aforementioned significant risk factors (small glenoid defect, ≤10%; medium or large bone fragment, >5%; and no capsular tear). Conclusion: Younger age at operation and preoperative glenoid defect with small or no bone fragment significantly influenced recurrent instability among competitive athletes.